EP060/#889 Patterns of care and treatment outcomes for elderly women with cervical cancer- are they different? – A retrospective analysis. (4th December 2022) - Gupta, Sudharshan; John, Neenu; Sathyamurthy, Arvind; Reddy, Jebakarunya Rami; Ram, Thomas
Abstract : Objectives: To evaluate the patterns of care and treatment outcomes in elderly patients with carcinoma cervix treated in our centre. Methods: We retrospectively analyzed the medical database of previously treated elderly patients diagnosed with carcinoma cervix between Jan 2013 to Dec 2018 after approval from the IRB. Results: The mean age of patients was 65 years (Range:60 -95). Of the 176 patients, 98 (56%) patients received only RT, 63 (35%) received CRT, five (3%) patients received adjuvant RT, 4(2.8%) patients received chemotherapy and 1 (0.5%) patient received palliative RT. The most common schedule used for EBRT(External beam radiotherapy) was 50 Gy in 25#, five days a week. The mean EBRT dose was 50 Gy (Range:46–54 Gy). 63 patients (37%) received concurrent cisplatin (dose of 40 mg/sq.m). Out of 161 patients who completed EBRT, 19 patients received EBRT boost, 133 patients underwent intracavitary brachytherapy. LDR was used in 48 patients and HDR was used in 85 patients. 2 patients underwent interstitial brachytherapy and mould brachytherapy was used in 8 patients. The median OTT was 69 days (9.8 weeks). Acute grade 3 GI toxicities were found in 21(12.8%) patients. The median follow-up duration was 22 months. Twenty patients had disease progression. The median PFS was 25 (18- 31) months and median OS was 27(18–35) months. 3 yr PFS was 37% and 5 yr PFS was 20%. 3 yr OS was 43% and 5 yr OS was 21%. Conclusions: To conclude, definitive radiotherapy comprising both EBRT and brachytherapy should be recommended even in the elderly women with careful assessment of comorbid conditions.